Suggestopedia Method in the Teaching and Learning Process (RETAIN, 2014)
Suggestopedia Method in the Teaching and Learning ProcessRagil KharismawatiEnglish Education Department, Language Art Faculty, State University of SurabayaEmail: ragil.kharismawati@yahoo.comProf. Dr. Susanto, M.Pd.English Education Department, Language Art Faculty, State University of SurabayaAbstrakAda empat tahap utama kegiatan dalam metode Sugestopedia. Mereka adalah presentasi, sesi konser (aktif dan pasif), elaborasi, dan praktek. Pada tahap presentasi, para siswa dibantu untuk mendapatkan pikiran positif bahwa belajar itu mudah dan menyenangkan. Dalam tahap ini, guru membuat lingkungan kelas menjadi nyaman dan ceria. Dalam konser aktif, guru membaca teks dan diulang oleh siswa. Setelah itu, dalam konser pasif, guru memainkan beberapa musik barok di latar belakang dan guru membaca teks lagi dan siswa mendengarkan dengan seksama. Dalam elaborasi, guru memberitahu siswa bahwa mereka akan melakukan sesuatu seperti membuat film, game, dll setelah sesi konser. Pada tahap prakteknya, guru menggunakan games, teka-teki, dll untuk meninjau pemahaman siswa. Penelitian ini bertujuan untuk menggambarkan kegiatan guru dalam tahap presentasi, sesi konser, panggung elaborasi, dan dalam tahap praktek.Peneliti memilih deskriptif kualitatif sebagai desain penelitian karena tujuan penelitian ini adalah untuk menggambarkan kegiatan guru selama pelaksanaan Metode Sugestopedia dan tidak ada treatment dalam penelitian ini. Peneliti berkonsentrasi pada salah satu guru bahasa Inggris yang mengajar di sekolah dasar di salah satu kota kecil di Jawa Timur. Data dalam penelitian ini diperoleh dari hasil observasi. Data dianalisis secara deskriptif untuk menjawab pertanyaan penelitian. Penulis menulis semua informasi tentang segala sesuatu yang terjadi selama proses belajar mengajar dalam bentuk catatan yang panjang.Hasil dan pembahasan adalah, pertama tahap presentasi metode Sugestopedia dilakukan untuk membuat siswa merasa bahwa belajar bahasa Inggris menyenangkan dan tidak memberatkan. Guru mengatur tempat duduk siswa menjadi setengah lingkaran untuk membuat siswa lebih nyaman dan dapat melihat papan tulis dengan baik. Kedua , dalam sesi konser , guru meminta siswa untuk mendengarkan dan mengulangi guru membaca teks di konser pertama ( konser aktif ) dan di konser kedua , guru meminta para siswa untuk merasa rileks , menutup buku mereka , dan mendengarkan guru membaca materi. Ketiga , dalam tahap elaborasi , guru mengingatkan siswa untuk pertama kalinya bahwa mereka akan melakukan permainan dan drama . Dan keempat , tahap akhir atau disebut tahap praktik , guru menggunakan permainan dan drama untuk memberikan latihan kepada siswa . Dari hasil tersebut , penulis dapat menarik kesimpulan kegiatan-kegiatan dari metode Suggestopedia dalam proses belajar mengajar dilakukan untuk membuat siswa merasa senang dan tertarik dalam proses belajar mengajar . Saran bagi guru agar menggunakan bahasa Inggris lebih sering dan bagi peneliti lain dapat melakukan penelitian serupa dalam aspek-aspek lain dari metode Sugestopedia .Kata Kunci: Suggestopedia, Metode, Proses Belajar Mengajar.AbstractThere are four main stages of the activities in suggestopedia method. They are presentation, concert session (active and passive), elaboration, and practice. In the presentation stage, the students are helped to get positive mind that learning is easy and fun. In this stage, the teacher sets the environment of the class as comfortable and cheerful as it could be for the students. In the active concert, the teacher reads a text and is repeated by the students. After that, in the passive concert, the teacher plays some baroque music in the background and she/he reads the text again and the students listen carefully. In the elaboration, the teacher tells the students that they will do something like making film, gaming, etc. after the concert session. In the practice stage, the teacher uses games, puzzles, etc. to review the studentsunderstanding. This research aims to describe the teacher activities in the presentation stage, concert session, elaboration stage, and in practice stage.The researcher chose descriptive qualitative as the research design because the aim of this study is to describe the activities of the teacher during the implementation of Suggestopedia Method and there was no treatment in this study. The researcher concentrated on one of English teacher who teach in elementary school in one of small cities in East Java. The data in this study was the result of observation field note. The data were analyzed descriptively to answer the research questions. The writer wrote all information about everything happened during the teaching-learning process in the form of long note.The results and discussion are first, the presentation stage of the suggestopedia method was done to make the students feel that learning English is fun and not stressing. The teacher arranged the students’ seats into semicircle to make the students more comfortable and can see the blackboard well. Second, in the concert session, the teacher asked the students to listen and repeat after her in the first concert (active concert) and in the second concert, asked the students to feel relax, close their book, and listen to the teacher reading the material. Third, in the elaboration stage, the teacher reminded the students for the first time that they are going to do game and drama. And fourth, the final stage or called practice stage, the teacher used games and drama to give practice to the students. From those results, the writer can draw a concusion that many activities of suggestopedia method in the teaching and learning process were done to make the students feel fun and interested in the teaching and learning process. The suggestion are to use English more often and for other researcher can do similar research in other aspects of suggestopedia method.Keywords: Suggestopedia, Method, Teaching and Learning ProcessINTRODUCTIONSuggestopedia is a teaching method that was introduced by Georgi Lozanov in 1970s. Lozanov (2005) states that suggestopedia is a teaching system which makes use of all the possibilities tender suggestion can offer. The suggestion here is about something that can make students feel enjoy in teaching and learning process. Lozanov created this method in the hope that students would enjoy in learning, especially learning foreign language. Suggestopedia was originally applied mainly in foreign language teaching, and it is often claimed that it can teach languages approximately three times as quickly as conventional methods. In that reason, the researcher is trying to conduct a research about suggestopedia.Lozanov (1978) states that there are four main stages of the activities in suggestopedia method. They are presentation, concert session (active and passive), elaboration, and practice. In the presentation stage, the students are helped to get positive mind that learning is easy and fun. In this stage, the teacher sets the environment of the class as comfortable and cheerful as it could be for the students. In the active concert, the teacher reads a text and is repeated by the students. After that, in the passive concert, the teacher plays some baroque music in the background and she/he reads the text again and the students listen carefully. In the elaboration, the teacher tells the students that they will do something like making film, gaming, etc. after the concert session. In the practice stage, the teacher uses games, puzzles, etc. to review the students understanding. The activities in suggestopedia method seem fun for the students. By applying this method in the class teacher hopes that the students will enjoy learning English.Many students in EFL classes think that learning foreign language is difficult. Gold, the founder of the National Council of Suggestopedia, said in his speech that suggestopedia was created to make easier learning for students because suggestopedia make the students feel fun and interested in the teaching and learning process. Lozanov (2005) also states that “if you want to learn more, more easily, more pleasantly, in a stable way and with a better impact on health – then accept Suggestopedia, desuggestive learning, because it is learning with love”. By applying the suggestopedia method, the students will feel that learning foreign language is not as difficult as they think. If the students feel that learning is easy and fun, they will be able to learn foreign language maximally.Lozanov (1978) argued that learners have difficulties in acquiring English as the second language because of the fear of the students to make mistakes. When the learners are in this condition, their heart and blood pressure raise. He believes that there is a mental block in the learners’ brain (affective filter). This filter blocks the input, so the learners have difficulties toacquire language caused by their fear. The aim of suggestopedia is to lower the affective filter and motivate students’ mental potential to learn, aiming to accelerate the process by which they learn to understand and use the target language for communication to achieve superlearning. It is the final goal of suggestopediaPriyatmojo (2009) found in his thesis that suggestopedia is useful in the teaching vocabulary to young learners. Suggestopedia helped the students to memorize well in vocabulary. It was good thing to use suggestopedia in the teaching and learning process. Djuhariah et.al. (2012) found that suggestopedia was also a good method in the teaching of reading to the twelfth grade students. They found that the students’ reading ability is improved by the applying the suggestopedia method in the teaching of reading. Meanwhile, Nopiyanti (2012) also found that suggestopedia is useful in the teaching of speaking to young learners. She found that the suggestopedia method can improve the speaking ability of young learners. From those researches, the suggestopedia method can be known as a method that useful in the teaching and learning process. That is why the researcher is trying to conduct a research about suggestopedia in the teaching and learning process of English class.Since the suggestopedia is a good method in the teaching and learning process of foreign language especially English, the researcher is trying to conduct a research about it. She is trying to do research in one of the class in one of schools in a small city of east Java. The researcher found that one of the teachers in that school is using suggestopedia in the English teaching and learning process. When the researcher was asking to that teacher, the teacher said that the students were very enthusiast in learning English when she applied suggestopedia method in the teaching and learning process. The way the teacher teaches English using suggestopedia makes the students feel fun and excited in learning English. The teacher uses music in class and makes the atmosphere in the class fun and the students feel that learning English is fun and interesting.There are many activities in suggestopedia method that can make students feel fun in the teaching and learning process. Therefore, there is no teacher who always uses suggestopedia method in the whole teaching and learning process in whole semester, the researcher is going to analyze the activities during the teaching and learning process that according to suggestopedia method. According to that reason, the researcher is going to do a research according to this research problem: What are the teacher’s activities in suggestopedia method in the teaching and learning process?Suggestopedia method is diferent from other method. Brown, cited in Nopiyanti (2012), stated that there are four main stages in suggestopedia. There are presentation, concert session, elaboration, and practice. These stages are important in the application of suggestopedia method. There are activities in every stage. The researcher was trying to analyze the activities during the teaching and learning process that using suggestopedia method according to those four stages. According to that reason, the researcher did a research according to the following research questions:a. What were the teacher’s activities in the presentation stage of suggestopedia method in the teaching and learning process?b. What were the teacher’s activities in the concert session of suggestopedia method in the teaching and learning process?c. What were the teacher’s activities in the elaboration stage of suggestopedia method in the teaching and learning process?d. What were the teacher’s activities in the practice stage of suggestopedia method in the teaching and learning process?The suggestopedia method has six key features that are important in the teaching and learning process using this method. According to Nosrati et. Al. (2013) the six key features of suggestopedia are:1. Comfortable environment2. The use of music3. Peripheral Learning4. Free Errors5. Homework is limited6. Music, drama and art are integrated in the learning processThe suggestion here is about the activities that can make students feel that learning is easy and fun. It is also believed that it can teach three times as quickly as a conventional method. This method has four stages, they are presentation stage, concert session (active concert and passive concert), elaboration, and practice stage (performance of the students).Lozanov (2005) stated that there are four stages in suggestopedia method, those are:a. Presentation StageThe main aim in this stage is to help students relaxed and move into a positive frame of mind, with the feeling that the learning is going to be easy and fun. In this stage, to make the students relax, teacher arranges the students’ seats in a comfortable way.At the teacher’s very first contact with the students, he or she introduces a spirit of easiness and delicacy into his or her attitude towards the group as a whole and towards each student as an individual. Instead of continuously playing in front of the students as if on a stage and before taking the decision to gradually involve them in the communication, the teacher now stimulates the students to join immediately and willingly in a common game project. The game project frees them from the boredom, demotivation, and fear of learning.b. Concert SessionsIn this concert session, Lozanov divided it into two parts. Those are active session and passive sessionThe first concert (active concert) involves the active presentation of the material to be learnt. For example, the teacher will read the text being studied and the students actively following the teacher’s reading. Here the teacher use some classical music and he or she reads the text in the harmony with the musical phrases. The musical compositions for the active session are emotional, with a wealth of melody and harmony in them.In this session, the students get the translation and are informed that, while the teacher is reading, they are looking at the text and the translation and only listen to the music – not to try to memorize. The teacher’s behavior is solemn, as it should be when the concert is about to begin.In reading, the teacher’s voice should be harmonized with the nuances of the musical phrase. The diction should be pure and distinct, every word clear-cut and phonetically well molded. The voice should be well taken up in the resonance box. The reading should be slow, and rhythmical, the breathing regular. The active session normally should not last more than 45-50 minutes.In the second concert (passive concert), the students are now invited to relax, close their book, and listen to some Baroque music, with the text being read very quietly in the background. The music is specially selected to bring the students into the optimum mental state for the effortless acquisition of the material. Brown (2007:27) stated that “during the soft playing of baroque music, one can take in tremendous quantities of material due to an increase in alpha brain waves and a decrease in blood pressure and pulse rate”. It can be said that by listening to baroque music, students can feel relax and it can make them smarter because it increase alpha brain waves.c. ElaborationElaboration of the material taught has actually begun at the first meeting of the teacher and the students. The first word the teacher says already open up a dialogue. For example, the teacher reminds the students in between that he or she and they are going together to prepare the material necessary for the film they plan to make. This is the systematic elaboration. The elaboration process should focus on the freedom and creativity of the students are encouraged even more than previously, all the stages of desuggestive pedagogy are unified during the elaboration through the use of reminding intonations, songs, the play, etc., the teacher continues to keep the students on the border of their linguistic knowledge. As well as facilitating spontaneous laughter and songs, the teacher purposefully puts jokes and songs into the lesson plan to help the students with the most difficult parts of the lesson.d. Practice StageThe practice stage is given the day after the second concert. Lozanov stated in Brown (2007: 28) stated that after the second concert the students will leave the class silently. They are not told to do any homework on the lesson they have just had except for reading it cursorily once before going to bed and again before getting up in the morning. In this stage teacher will not do something stressful for students practice. The teacher uses a range of games, puzzles, etc. to review and consolidate the learning.METHODSBased on the research problems and the objective of the study, the researcher used descriptive qualitative as the research design. The aim of descriptive qualitative is to describe a real situation or phenomenon,and the researcher took place as an observer only. The researcher did not take a part in teaching learning process. She only observed the teacher’s activities in the class and reported the activities from beginning up to the end of the class. This research took place in a natural setting, without any attempts to manipulate the situation under the study.Bogdan and Biklen (1982) in Sugiyono (2011) say that the characteristic of qualitative research are; has natural setting as the direct source of data, the data collected is in the form of words or picture rather than number, it is concerned with process rather than simply with outcomes or products, it tends to analyze the data inductively. Those mean the researcher should give a real phenomenon, not manipulated data. In the qualitative research, the researcher reports the data in descriptive way.So, here the researcher conducted a research and described all of the data she needed. She came to the class and she sat on the back seat. She was an observer, which meant she only observed the classroom activities and she did not disturb the class by whatever she did. She observed the class and described the teacher’s activities.The study was set in one of an Elementary school in one of small cities in East Java. There are six classes and one English teacher in that school. The English lesson was taught from the second until sixth grade. So that, there are only five classes which are taught English lesson. The researcher chose fourth grade because this class was in the middle among the other classes.The subject of this study was an English teacher in one of elementary schools in a small city in East Java Indonesia. The researcher did a research about the teacher’s activities during teaching and learning process. These activities included the activities in the suggestopedia method.The Data of the study were the activities in the teaching and learning process that were according to suggestopedia method. To get the data, the researcher wrote field notes to observe the teacher’s activities in the teaching and learning process. The data were classified into four data to answer the research questions of this thesis.The first data were about the teacher’s activities in the presentation stage of suggestopedia method in the teaching and learning process. These data were to answer the first question “what were the teacher’s activities in the presentation stage of the suggestopedia method in the teaching and learning process?”The second data were about the teacher’s activities in the concert session of the suggestopedia method in the teaching and learning process. These data were to answer the second question “what were the teacher’s activities in the concert session of the suggestopedia method in the teaching and learning process?” The concert session of the suggestopedia method were divided into two. Those were the first concert or active concert and the second concert or passive concert.The third data were about the teacher’s activities in the elaboration session of the suggestopedia method in the teaching and learning process. These data were to answer the third research question “what were the teacher’s activities in the elaboration stage of the suggestopedia method in the teaching and learning process?”The fourth data were about the teacher’s activities in the practice stage of the suggestopedia method in the teaching and learning process. These data were to answer the fourth research question “what were the teacher’s activities in the practice stage of the suggestopedia method in the teaching and learning process?”To collect the data, the researcher used observation technique as a qualitative one. Here, the researcher did no-participant observation. It means she did not participate directly and influence in the teaching and learning process. In this research, the researcher used observation field notes. She used this observation because she wanted to find out the activities done by the teacher while she was applying the suggestopedia method. The researcher did this observation by writing all the activities of the teacher while the teaching learning process was held.The data of this study was analyzed qualitatively using descriptive analysis. From the field note the researcher analyzed them descriptively. There were some steps to describe and analyze the data. They are: The researcher collected all the data from field notes, the researcher organized the data during the observation, and then decided what have to be reported, after analyzing the data, the researcher described the data by classifying them into parts based on the problems of the study, the researcher tried to make conclusion.RESULTS AND DISCUSSIONSThe results and discussions is the answer of the problems in introductions. The data were taken through the observation and only focused on teacher activities during the implementation of suggestopedia method in the teaching and learning process.1. The Implementation of Suggestopedia Method in the Teaching and Learning ProcessThe data were obtained through the observation that was focused in the teachers’ activities during the implementation of Suggestopedia method in the teaching and learning process. There are six key features of suggestopedia method. They are comfortable environment, the use of music, peripheral learning, free errors, homework is limited, and music, drama, and art are integrated in the teaching and learning process.The teaching and learning process of suggestopedia method had a comfortable environment. The chairs were arranged into semicircle facing the blackboard so that the students can pay more attention to the teacher and would be more relaxed. The teacher also always asks for the students’ condition whether they were comfortable enough or not in the day they study English. There are many pictures on the wall that can support their teaching and learning process. Those pictures are there in the hope that when the students forget about something they can get it from the wall immediately.Nosrati et. al. (2013) state that in this kind of teaching method, suggestopedia method, the classroom is very different from common classrooms. In the classroom, the chairs are arranged semicircle and faced the black or white board in order to make the students pay more attention and get more relaxed. The teacher arranged the students’ chair into semicircle to make the students feel more relax.The teacher used baroque music in the suggestopedia teaching and learning process. Baroque music is a classic music. In the suggestopedia method baroque music is used to make the students more relax. If the students are relaxed, their feeling of fear will be decreased and it can make the students easier to understand while studying English. The teacher asked the students to listen to the music and feel more relax.One of the most uniqueness of this method is the use of Baroque music during the learning process (Nosrati et. al., 2013). Ostrander and Schroeder cited in Harmer (1998) said that Baroque music, with its 60 beats per minute and its specific rhythm, created the kind of relaxed states of mind for maximum retention of material. It is believed that Baroque music creates a level of relaxed concentration that facilitates the intake and retention of huge quantities of materials.In the suggestopedia method, students were in a peripheral learning. The students acquire English not only from direct instruction but also from indirect instruction. It is encouraged through the presence in the learning environment of posters and decoration featuring the target language and various grammatical information (picture 1).Picture 1: There are many pictures on the wallWhen the students got something confusing, they can take a look at the wall and see whether they can get the information they need on the wall directly so that their confusion can be answered quickly. Nosrati et. al. (2013) stated that by doing this, putting many pictures on the wall, the students can learn many things undirectly in the classroom.The teacher tolerated the students if they made some errors while teaching and learning process. By doing this, the students did not feel afraid of doing something in the class like saying something they wanted to say.(1)TSTSTST::::::::“Touch your foot”(They touch their foot)“Touch your shoulders”(some of them touch their shoulders and some of them touch their ears)“Ayoo kok ada yang pegang kuping? Shoulders tu apa cah? Pun….Pundak. ““O iya bu.. pundak..” (They touch their shoulders)“ok Good. Gak papa masih adayang salah dikit-dikit.In dialog one (1) some of the students made mistakes when the teacher asked them to touch their shoulders but the teacher said that it’s ok to make mistakes. When the students were allowed to make mistakes, they would not afraid of trying something that they were not sure about. If they were trying something, it means that they were trying to studying something new. If the teacher just stops them when they make a mistake, it will make them afraid of trying something new. In other words, the learning process will end when the students stop trying something new. Nosrati et. al. (2013) stated that in the teaching learning process, students who make mistakes are tolerated. The emphasis is on the content not the structure. Grammar and vocabularies are presented and given treatment from the teachers, but not dwelt on.In the suggestopedia method teacher also did not give too much homework to the students. It was not because she did not want the students to study at home but it was because the teacher wanted the students to study their last material once they want to go to bed and once they get up in the morning.(2)TST:::“anak-anak, sekarang sudah saatnya pulang, sebelum kita pulang saya mau kalian nanti dirumah membaca materi yang telah kita pelajari hari ini sebelum tidur dan besuk pagi waktu kalian bangun tidur ya..’“iya bu..”“baiklah, ketua kelas silakan memimpin berdoa”.In the dialog two (2), the teacher did not forget to remind the students to read their last material once they want to go bed and once they get up in the morning. It is also stated in Nosrati et. al. (2013) that Students reread materials given in the classroom once before they go to sleep at night and once in the morning before they get up. This assignment was more appropriate than giving the students much homework to do at home. If the teacher gives much homework to do at home, the students will think that English is frustrating lesson with much homework.The use of music, drama, and art were integrated in the teaching and learning process of suggestopedia method. The teacher asked the students to sing together in the class. This was done to make the students feel fun and to make the students easier to study English if they were in a fun condition. The teacher also used drama in the teaching and learning process and this also made the students felt fun in the teaching and learning process.2. The teacher’s Activities in the Presentation Stage of Suggestopedia Method in the Teaching and Learning ProcessThe first problem of the implementation of suggestopedia method in the teaching and learning process was the teacher’s activities in the presentation stage of suggestopedia method in the teaching and learning process. Lozanov (2005) stated that the main aim of this stage is to help students relaxed and move into a positive frame of mind, with the feeling that the learning is going to be easy and fun. The teacher began with the seats of the students. She arranged the students’ seats into semicircle facing the blackboard (picture 2).Picture 2: The chairs were arranged semicircleLozanov (2005) stated in this stage, to make the students relax, teacher arranges the students’ seats in a comfortable way. In this condition, the students felt more relax and could clearly see the teacher and the blackboard. The teacher also could clearly see the students.In this stage, the teacher used music or song to make the students feel fun and happy before having the material. The song also one of the activities for listening and speaking comprehension because they first listen to the teacher singing the song, then they sang it together with the teacher. In the dialog three (3) stated that the teacher asked the students to sing and the students were very happy to be asked to sing together with the teacher. The song they sang was related to the material they were studying that day. The material that day was about parts of body and the song was “Head Shoulders Knees and Toes”. In other words, by singing the song, the students could also memorize the parts of body.Teachers also paid attention to the students' ability to receive a singing material given by the teacher because the teacher did not want the students to feel uncomfortable if the song was too difficult for students. If the song was too difficult then the students would not feel happy but they would feel stressed.(3)TSPutriT::::“susah gak lagunya?”“ndak bu..”“itu lagu kepala pundak lutut kaki ta bu?”“yes, you’re right putri, bener banget, tapi ini yang versi inggrisnya”“ok, sekarang kita dengarkan sekali lagi terus kita nyanyi bareng-bareng ya..”In dialog three (3) the teacher made sure that the students did not find difficulties in singing the song. She did not want that the students would feel that learning English is difficult if she gave a difficult material in the English class. As stated in Lozanov (2005) at the teacher’s very first contact with the students, he or she introduces a spirit of easiness and delicacy into his or her attitude towards the group as a whole and towards each student as an individual.3. The teacher’s Activities in the Concert Session of Suggestopedia Method in the Teaching and Learning ProcessThe second problem of the implementation of suggestopedia method in the teaching and learning process was about the teacher’s activities in the concert session of suggestopedia method. After the presentation stage, the teacher directly moved into the concert sessions. There were two kinds of concert sessions, the first was the active concert and the second was passive concert.a. First Concert (Active concert)The first concert or called active concert involved the active presentation of the material to be learnt. This meant that the students were active in the teaching and learning process. Here the teacher used some classical music and he or she read the text in the harmony with the musical phrases. In the research the researcher did before, the students were actively following the teacher’s reading the material. This activity was one of the speaking comprehension activities because the students actively following the teacher’s reading that means they are reading aloud the text. The reading aloud was according to speaking activities.Lozanov (2005) stated that in this session, the students get the translation and are informed that, while the teacher is reading, they are looking at the text and the translation and only listen to the music – not to try to memorize. The teacher wanted the students to recognize the text well before going to go to comprehend the text.After the first reading without any translation, the teacher then began to read the text and translate the text together with the students. The teacher used gesture and sometimes song to remind the students about the translation of some words. This meant that the students also actively translating the text being studied with the teacher.b. Second Concert (Passive Concert)The second concert is called passive concert. Lozanov (2005) stated the students are now invited to relax, close their book, and listen to some Baroque music, with the text being read very quietly in the background. This activity refers to listening comprehension. The music is specially selected to bring the students into the optimum mental state for the effortless acquisition of the material.In dialog eight (8) the teacher asked to the students to close their book and listen to her reading the dialog. In this concert session, the baroque music was still played as background music. The baroque music was still used because it made the students more relax and could think better when they were relaxed as stated in Brown(5)TST:::“ok students, sekarang saya akan membacakan dialog yang ada di halaman 37 between Rendra and Reza. Please listen and repeat ya.”“iya bu”“nanti kalian harus maju berdua satu bangku untuk memperagakan dialognya, jadi dengarkan dan tirukan baik-baik”(4)T:“Ok students, now it’s time to close your book and listen to me. Tutup buku dan dengarkan saya baik-baik ya. Saya akan membacakan dialognya sekali lagi sebelum kalian nanti maju membacakan dialognya di depan kelas. Ok?”(2007:27) “during the soft playing of baroque music, one can take in tremendous quantities of material due to an increase in alpha brain waves and a decrease in blood pressure and pulse rate”. It can be said that by listening to baroque music, students can feel relax and it can make them smarter because it increase alpha brain waves.4. The teacher’s Activities in the Elaboration of Suggestopedia Method in the Teaching and Learning ProcessElaboration of the material taught has actually begun at the first meeting of the teacher and the students. The first word the teacher says already open up a dialogue. For example, the teacher reminds the students in between that he or she and they are going together to prepare the material necessary for the film they plan to make.In the research the researcher did at school, the teacher did the elaboration stage in the first time she arrived at the first concert session.In dialog five (5) the teacher would read the dialog on the book between Rendra and Reza. But before she read, she reminded the students that they would come forward to perform the dialog with their seat mate. This was an elaboration stage activity. This elaboration had a purpose to make the students more aware or ready for something they do in the future. In that case, the students would listen and repeat seriously because they do not want to get a bad score if they come forward.Besides reminding the students that they would come forward to perform a dialog, the teacher also did the elaboration when she’s explaining about the material the students did not know.In dialog 6 the teacher also did the elaboration. She sang a song to remind the students about the question “how many”. She did not immediately tell the students the meaning of the question “how many” because she wanted the students to think about it themselves in the helped of her song. Besides singing the song, the teacher also remind the students about the meaning of “fingers” by saying “I have ten fingers” and showing her fingers to the students and finally the students knew the meaning of fingers. Lozanov (2005) states that the elaboration process should focus on the freedom and creativity of the students are encouraged even more than previously, all the stages of desuggestive pedagogy are unified during the elaboration through the use of reminding intonations, songs, the play, etc., the teacher continues to keep the students on the border of their linguistic knowledge.5. The teacher’s Activities in the Practice Stage of Suggestopedia Method in the Teaching and Learning ProcessThe practice stage is the last stage of suggestopedia method. In this stage the teacher can measure the students’ comprehension of the material they had learned before. According to Lozanov in Brown (2007), practice stage is given to the students the day after the concert session. Otherwise, the teacher in the research the researcher did before gave the practice stage on the same day with the concert session. It was due to the teacher still had much time to do the practice stage. It was also good to give the students the practice stage on the same day with the concert session as long as the practice stage did not stress the students.The teacher did games, drama, and writing a video clip lyric during the practice stage of her suggestopedia class. The first game was named “Simon Says”. In this game, the teacher checked the vocabulary of the students about parts of body. The teacher also could check the listening comprehension of the students.The second game was given by the teacher for the students named “Parts of body game” This game was a power point game. Before starting the game, the teacher explained about the rule of the game and how to play the game. After the students had understood about the rule of the game, the teacher began to start the game.(6)TSTSTSTSTST:::::::::::“Bagus, saya akan memberikanmu beberapa pertanyaan. How many fingers do you have? How many menanyakan apa?”(they are confused and talk to each other discussing)“masa lupa?” (then singing) “What apa, who siapa, how bagaimana….”“bagaimana bu..”“alright, how itu bagaimana, tapi kalo ditambah sama many jadi how many artinya berapa..jadi how many fingers do you have? Fingers apa?”(thinking)“I have ten fingers” (showing her ten fingers to the students)“Jari bu”“Good, jadi artinya how many fingers do you have?”“berapa jari yang kamu punya?”“Good”There were several questions in the game. They were related to the text. By doing this game, the teacher could measure the reading comprehension of the students.The other practice stage did by the teacher was drama. For the fourth grade students, it was difficult for them to memorize the script of the dialog. So that, the teacher asked the students to bring the dialog script in front of the class. In other words the students read the dialog in front of the class. It was a kind of drama.The teacher also did a writing practice to the students to know the writing ability of the students. The teacher showed the students a video clip. The title of the song was “If you’re happy”. The video had the lyric on it so that the students could read the lyric of the song. Then the teacher asked the students to write the lyric of the song on their book.In practice stage, the teacher did fun activities to review the students understanding. Lozanov (2005) states that in this stage teacher will not do something stressful for students practice. The teacher uses a range of games, puzzles, etc. to review and consolidate the learning.CONCLUSIONS AND SUGGESTIONSConclusionThe major problem of this study is the teachers’ activity during the implementation of Suggestopedia method in the teaching and learning process. The main problem that is developed based on the teacher activity during the suggestopedia method in the teaching and learning process devided into four, they are: (1) The teacher’s activities in the presentation stage of suggestopedia method in the teaching and learning process, (2) The teacher’s activities in the concert session of suggestopedia method in the teaching and learning process, (3) The teacher’s activities in the elaboration stage of suggestopedia method in the teaching and learning process, (4) The teacher’s activities in the practice stage of the suggestopedia method in the teaching and learning process.Based on the findings of data analysis and discussion in the previous chapter, the researcher drew a conclusion: first, the teacher’s activities in the presentation stage of suggestopedia method in the teaching and learning process was going well. The presentation stage of the suggestopedia method was done to make the students feel that learning English is fun and not stressing. The teacher arranged the students’ seats into semicircle to make the students more comfortable and can see the blackboard well. The teacher also asked the students to sing together to make the students happy. Second, in the concert session, the teacher asked the students to listen and repeat after her in the first concert (active concert) and asked the students to feel relax, close their book, and listen to the teacher reading the material. Third, in the elaboration stage, the teacher reminded the students for the first time that they are going to do game and drama. This stage was to make the students more concentrated to the lesson. And fourth, the final stage or called practice stage, the teacher used games and drama to give practice to the students. In the practice stage the teacher used games and drama to make the students think that practice is not something stressful.SuggestionsAt the end of this study, some suggestions are offered related to the result of the study. The result of this study was the teacher did well in the presentation stage, concert session, elaboration stage, and practice stage of suggestopedia method in the teaching and learning process, but to become a profesional teacher she also must have the other aspect, having a good teaching skill. Therefore first, the researcher suggest to the teacher to consider about language use that she choose. Second, the researcher suggests to other researchers to conduct a similar study, but they can view from the other aspects such as the grade levels of education, and various type of genre.ReferencesBrown, H.,D. 2007. Teaching by Principles – An Interactive Approach to Language Pedagogy. Pearson Education, Inc.Djuhariah, et.al. 2012. Improving Students’ Reading Comprehension of Narrative Text Through Suggestopedia Method. Unpublished Research: Tanjungpura University Pontianak.Gold, Lonny. The Speech of Suggestopedia – Activating the Students Reserve Capacities. 17 June 2013 < www.youtube.com/watch?v=yX4JFEUgqlg>.Halliwell, Susan. 1992. Teaching English in the Primary Classroom. Longman: New York.Harmer, Jeremy. 1998. How to Teach English. Malaysia: LongmanLica, Gabriela Mihaila. 2008. Suggestopedia: A Wonder Approach to Learning Foreign Languages. Assian EFL Journal: English Language Teaching and Research Article. 17 June 20013 http://www.jalt-publications.org/tlt/files/97/feb/suggest.html.Lozanov, G. 2005. Suggestopaedia-Desuggestive Teaching Communicative Method on The Level of The Hidden Reserves of the Human Mind. International Centre for Desuggestology: Austria.Lozanov, G. 1978. Suggestology and Suggestopedia – Theory and Practice. Bulgaria: United Nations Education, Scientific and Cultural Organization.Nopiyanti, M.,S. 2012. Teaching English Speaking Using Suggestopedia Method at the Fourth Grade Students of SD Mutiara Nusantara parongpong. Unpablished Thesis: STKIP Siliwangi Bandung.Nosrati, et.al. 2013. Investigation of Language Teaching Methodologies in Second Language Learning. International Journal of Economy, Management and Social Sciences.Nunan, David (Ed). 2003. Practical English Language Teaching. Singapore: Mc Graw Hill.Priyatmojo, A.S. 2009. Suggestopedia as a Method for Teaching Speaking for Young Learners in a Second Language Classroom. Semarang State University: Unpublished Thesis.Radle, Paul. 2008. Suggestopedia. 17 Nov.2013 http://www.vtrain.net/lang-sugg.htm.Sugiyono. 2011. Metode Penelitian Kuantitatif Kualitatif dan R&D. Bandung: Alfabeta, cv.Zainuddin et.al. 2011. Methods/Approaches of Teaching ESOL: A Historical Overview. Kendall Hunt Publishing Co.